Building a practical curriculum in clinical ethics and responsible research for undergraduate medical students in Guatemala - Maria-Lorena Ag; Sergio Martinez; Francis Barchi (Elsevier, 2018)
Background: Despite growing concerns over unprofessional conduct by physicians and medical trainees in the Guatemalan health system, little has been done to develop a practical curriculum in clinical ethics and responsible research for undergraduate medical students in Guatemala. As part of a training programme in ethics education supported by the US National Institutes of Health's Fogarty International Center, faculty at Universidad Francisco Marroquin (UFM) in Guatemala City aimed to incorporate active-learning ethics short-courses into an existing system of credit-bearing electives offered to students as part of their 6-year undergraduate medical education. Methods: Two preliminary workshops led by Guatemalan faculty trainees with the assistance of US mentors from Rutgers University, Johns Hopkins University, and the University of Pennsylvania, were used to stimulate student interest in future ethics courses, illustrate the level of student demand, and provide an evidence base to guide the development of a formal curriculum. Findings: The resulting ethics course includes six 2-h modules, each of which is a stand-alone unit with learning goals and objectives, assigned readings, a discussion case, and assessment. These structured case-based activities allow for flexibility in design and scheduling, do not compete with core requirements of the existing curriculum, and enable students to develop critical reasoning approaches to ethical situations they will encounter in medical practice. The courses enhance rather than challenge existing bioethics content that historically emphasised moral and religious doctrine but did little to develop practical skills. The course, which targets second and third year medical students, has thus far been offered twice, and two additional sessions are scheduled during the current academic year. To date, more than 80 students have participated in the workshops and courses. Evaluations are being used to refine pedagogical approaches and drive course content. Interpretation: The UFM ethics elective courses offer a model for transforming medical ethics education in undergraduate medical programmes throughout Guatemala and the region. Funding: None.